THE CORRELATION BETWEEN ATTITUDES AND DISCIPLINE TOWARD SCIENCE OF SECONDARY SCHOOL - Astalini Astalini; Haerul Pathoni; Dwi Agus Kurniawan; Nugroho Kurniawan (Universitas Negeri Malang, 2019)
Abstract: The purpose of this research was to study the attitudes and discipline of secondary school students in Indonesia and its correlation between those two characters. This was a survey study with total sampling technique of 612 respondents. The grade of discipline and attitutes were measured according to Lickert scale, while the correlation between discipline and attitude was analyzed using Pearson correlation calculation. Based on the results of the study, both the attitude and the discipline of students towards science is good. This research also revealed a significant positive correlation between students' attitudes and discipline. Grade 7th showing the strongest correlation, and it is decreasing by the grade, with the weakest was showed by grade 9th. Key Words: attitude towards science, discipline toward science, secondary school students Abstrak: Penelitian ini bertujuan untuk meninjau sikap dan kedisiplinan siswa tingkat sekolah menengah di Indonesia serta hubungan dua karakter tersebut. Penelitian ini merupakan survei dengan mengambil sampel sebanyak 612. Tingkat kedisiplinan dan sikap diukur berdasarkan skala Lickert, sedangkan korelasi antara disiplin dan sikap dianalisis menggunakan perhitungan korelasi Pearson. Berdasarkan hasil penelitian, sikap dan disiplin siswa terhadap sains menunjukkan hasil yang baik. Penelitian ini juga mengungkapkan korelasi positif yang signifikan antara sikap dan disiplin siswa. Korelasi terkuat terdapat pada siswa kelas 7, dan menurun berdasarkan tingkatan kelas, dengan korelasi yang terlemah pada kelas 9. Kata kunci: sikap terhadap sains, disiplin terhadap sains, siswa sekolah menengah